The strategy for enhancing temozolomide against malignant glioma - Nakada, Mitsutoshi; Furuta, Takuya; Hayashi, Yutaka; Minamoto, Toshinari; Hamada, Jun-ichiro (Frontiers in Oncology, 2012)
A combined therapy of the alkylating agent temozolomide (TMZ) and radiotherapy is standard treatment, and it improves the survival of patients with newly diagnosed glioblastoma (GBM). The DNA repair enzyme O6-methylguanine-DNA methyltransferase (MGMT) removes the most cytotoxic lesions generated by TMZ, O6-methylguanine, establishing MGMT as one of the most important DNA repair mechanisms of TMZ-induced DNA damage. Thus, the expression of MGMT, its activity, and its promoter methylation status are associated with the response of GBM to TMZ, confirming that MGMT promotes clinical resistance to TMZ. Previous studies have shown that a variety of drugs such as interferon-β, levetiracetam, resveratrol, and valproic acid increased the sensitivity of TMZ through MGMT-dependent or MGMT-independent mechanisms. In this review, we describe drugs and promising molecules that influence the responsiveness of GBM to TMZ and discuss their putative mechanism of action. In MGMT-positive GBMs, drugs that modulate MGMT activity could enhance the therapeutic activity of TMZ. Thus, administration of these drugs as an adjunct to TMZ chemotherapy may have clinical applications in patients with malignant gliomas to improve the outcome.